Correlation between estimated glucose disposal rate and in-stent restenosis following percutaneous coronary intervention in individuals with non-ST-segment elevation acute coronary syndrome - Liu, Chi; Zhao, Qi; Zhao, Ziwei; Ma, Xiaoteng; Xia, Yihua; Sun, Yan; Zhang, Dai; Liu, Xiaoli; Zhou, Yujie (Frontiers in Endocrinology, 2022)
Background Insulin resistance (IR) is closely associated with in-stent restenosis (ISR) following percutaneous coronary intervention (PCI). Nevertheless, the predictive power of the newly developed simple assessment method for IR, estimated glucose disposal rate (eGDR), for ISR after PCI in individuals with non-ST-segment elevation acute coronary syndrome (NSTE-ACS) remains unclear. Methods NSTE-ACS cases administered PCI in Beijing Anzhen Hospital between January and December 2015 were enrolled. The included individuals were submitted to at least one coronary angiography within 48 months after discharge. Patients were assigned to 2 groups according to ISR occurrence or absence. eGDR was derived as 21.16 - (0.09 * waist circumference [cm]) - (3.41 * hypertension) - (0.55 * glycated hemoglobin [%]). Multivariate logistic regression analysis and receiver operating characteristic (ROC) curve analysis were performed for evaluating eGDR’s association with ISR. Results Based on eligibility criteria, 1218 patients were included. In multivariate logistic analysis, the odds ratios (ORs) of eGDR as a nominal variate and a continuous variate were 3.393 (confidence interval [CI] 2.099 - 5.488, P < 0.001) and 1.210 (CI 1.063 - 1.378, P = 0.004), respectively. The incremental effect of eGDR on ISR prediction based on traditional cardiovascular risk factors was reflected by ROC curve analysis (AUC: baseline model + eGDR 0.644 vs. baseline model 0.609, P for comparison=0.013), continuous net reclassification improvement (continuous-NRI) of -0.264 (p < 0.001) and integrated discrimination improvement (IDI) of 0.071 (p = 0.065). Conclusion In NSTE-ACS cases administered PCI, eGDR levels show an independent negative association with increased ISR risk.